0064 Deep-brain Imaging Of Lateral Hypothalamic vGAT Neurons During Sleep. (12th April 2019) - Blanco-Centurion, Carlos; Luo, Siwei; Vidal-Ortiz, Aurelio; Sun, Ying; Zou, Bingyu; Shiromani, Priyattam; Liu, Meng
Abstract: Introduction: In-vivo electrophysiology has identified neurons that are selectively active in waking, NREM, or REM sleep (for review see Shiromani and Peever, 2017). However, this method has limitations. New tools are needed to disentangle the brain circuitry regulating complex behaviors such as sleep. We use deep-brain imaging to measure calcium (Ca2+) gradients associated with excitatory signaling (Tian et al., 2009)(Ghosh et al., 2011) in neurons that contain the vesicular GABA transporter (vGAT). The vGAT neurons are a distinct population juxtapositioned with the neurons that contain orexin or MCH in the lateral hypothalamus (Blanco-Centurion et al., 2018), but their activity in sleep in freely-behaving animals is unknown. Methods: In vGAT-cre mice, rAAV-DIO-GCaMP6m was delivered stereotaxically to the lateral hypothalamus (isofluorane anesthesia) and a GRIN lens and sleep electrodes were implanted. Three weeks later a miniscope (nVista; Inscopix.com) revealed single vGAT neurons. Results: Thirty-eight vGAT neurons were automatically extracted (PCA-ICA analysis; Mosaic software) from three vGAT-cre mice (female). The average fluorescence was significantly higher during both active wake and REM sleep compared to QW, NREM or REM transition [F(4, 175)=14.05; P=0.001; Mixed Model SPSS25]. The fluorescence in NREM was the lowest compared to the other states [P=0.001]. In REM sleep and active waking, the fluorescence occurred in phasic volleys. Conclusion: The activity of the vGAT neurons in the lateral hypothalamus is similar to the activity of the vGAT neurons in the amygdala, and suggests that these neurons may respond to activity in the sensory-motor system during active waking and REM sleep. References Blanco-Centurion, C., Bendell, E., Zou, B., Sun, Y., Shiromani, P.J. & Liu, M. (2018) VGAT and VGLUT2 expression in MCH and orexin neurons in double transgenic reporter mice. IBRO Rep, 4, 44-49. Ghosh, K.K., et. al., (2011) Nat Meth, 8, 871-878. Shiromani, P.J. & Peever, J.H. (2017) Sleep, 40 . Tian, L., et. al., (2009) Nature methods, 6, 875-881. Support (If Any): NIH: NS052287, NS079940, NS098541, NS096151 (ML), NS101469 (ML); and Veterans Affairs (BX000798). Dr. Shiromani is the recipient of a Senior Research Career Scientist Award (1K6BX004216) from the Department of Veterans Affairs.